2006
DOI: 10.1128/mcb.26.4.1569-1577.2006
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role for Protein Kinase D Family Kinases in the Regulation of Class II Histone Deacetylases in B Lymphocytes

Abstract: We have taken a knockout approach to interrogate the function of protein kinase D (PKD) serine/threonine kinases in lymphocytes. DT40 B cells express two PKD family members, PKD1 and PKD3, which are both rapidly activated by the B-cell antigen receptor (BCR). DT40 cells with single or dual deletions of PKD1 and/or PKD3 were viable, allowing the role of individual PKD isoforms in BCR signal transduction to be assessed. One proposed downstream target for PKD1 in lymphocytes is the class II histone deacetylases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 53 publications
4
132
0
1
Order By: Relevance
“…Unexpectedly, a recent study reported a newly developed PKD1-selective inhibitor failed to attenuate PCH in whole animal models (31). One possible explanation for such a discrepancy is that PKD3 could substitute for PKD1 as a HDAC5 kinase as documented in non-cardiac cells (32). Our new results shown herein indicate PKD3 is indeed required for PCH but works through a different mechanism.…”
Section: Pathological Cardiac Hypertrophy (Pch)mentioning
confidence: 53%
“…Unexpectedly, a recent study reported a newly developed PKD1-selective inhibitor failed to attenuate PCH in whole animal models (31). One possible explanation for such a discrepancy is that PKD3 could substitute for PKD1 as a HDAC5 kinase as documented in non-cardiac cells (32). Our new results shown herein indicate PKD3 is indeed required for PCH but works through a different mechanism.…”
Section: Pathological Cardiac Hypertrophy (Pch)mentioning
confidence: 53%
“…[37][38][39][40] To extend results from T lymphocytes, we studied exosome secretion in DT40 chicken B lymphocytes that lacked their two PKD isotypes, PKD1 and PKD3. 36 Wild-type and PKD1 − / − 3 − / − DT40 cells were transfected with GFP-CD63 and exosome secretion was assessed after stimulation with PMA plus ionomycin or with anti-IgM. PMA plus ionomycin induced exosome secretion in WT, but not in .…”
Section: Resultsmentioning
confidence: 99%
“…While this molecular heterogeneity is generally assumed to reflect the co-expression of multiple PKD isoforms with distinct cellular functions, direct experimental evidence that native PKD isoforms are activated in a stimulusspecific manner and/or phosphorylate different target substrates in vivo in a cellular context has never been published. In fact, studies using either RNA interference technology or genetic knock-out strategies generally identify functionally redundancy for individual PKD isoforms (2,10). This study is the first to show that PKD1 and PKD2 are activated in an agonist-specific manner in cardiomyocytes.…”
Section: Protein Kinase D (Pkd)mentioning
confidence: 86%